1999
DOI: 10.3168/jds.s0022-0302(99)75277-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Smoothing of Lactation Curves with Cubic Splines

Abstract: Most approaches to modeling lactation curves involve parametric curves with fixed or random coefficients. In either case, the resulting models require the specification on an underlying parametric curve. The fitting of splines represents a semiparametric approach to the problem. In the context of animal breeding, cubic smoothing splines are particularly convenient because they can be incorporated into a suitably constructed mixed model. The potential for the use of splines in modeling lactation curves is explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
130
2
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(149 citation statements)
references
References 6 publications
14
130
2
3
Order By: Relevance
“…Using the sum may be reasonable if the genetic influence is constant over time. However, studies have shown that correlations between measurements differ over the lactation [2,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the sum may be reasonable if the genetic influence is constant over time. However, studies have shown that correlations between measurements differ over the lactation [2,24].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that these biological components influence the QTL expression, which will result in non constant QTL effects over time. In fact evidence from polygenic studies suggest that the additive genetic variance changes over lactation stages for production traits in dairy cattle [2,7,18,24].…”
Section: Introductionmentioning
confidence: 99%
“…Regression splines (White et al, 1999) were used to model lactation curves. Six-knot regression splines, with knots positioned at days 7, 20, 50, 135, 245 and 335, were considered to be an accurate way to model lactation curves (Druet et al, 2003).…”
Section: Datamentioning
confidence: 99%
“…These models differ in the way the lactation curve is modelled as a function of days in milk (DIM), with fixed classes, parametric or semi-parametric (splines) curves; in the way the genetic and permanent environment components are described (fixed or random regression using Legendre or other polynomials); and in the way heterogeneous residual variances are accounted for. In France, regression splines (White et al, 1999) were chosen to model lactation curves (Druet et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Future research should investigate alternative, more parsimonious models. On the one hand, these could include parametric curves (linearised if applicable) or splines, similar to applications to model test day yields in dairy cattle (see [4] and [42], respectively). On the other hand, there may be scope to reduce the number of parameters by modelling the within animal, permanent environmental covariance structure invoking a parametric correlation function described by one or two parameters in conjunction with a variance function to allow for heterogeneous variances (e.g.…”
Section: Alternative Modelsmentioning
confidence: 99%